Información clandestina - Hernández Les, Juan Antonio (Estudios sobre el Mensaje Periodístico, 2002)
This article is born of idea what is possible to propone, from the comparative method, a methodic articulation of conceptual “clandestine information”, imputing to the media one series of characteristics within a diachronic historical context, starting off of models that find in the cinema, the radio and the press, own signals of informative identity, with special relevance of facts happened in Spain and other foreign countries. When beginning in the Spanish civil war, and closing the circle in the Spanish political transition, the work includes an ample historical process, of more than 40 years than it invites the investigators to lend the interest that deserves the journalism when this one is surrounded by the starvation and lack of freedom
Keywords: Documentary cinema; editing cinema; film tract; resistance; Camus; Combat; American Activities Committee; critic journalism